Effects of Dietary Rosemary Essential Oil on Growth Performance, Carcass Traits and Some Hematological Values of Chukar Partridge - Behlül Sevim; Erinç Gümüş; Halil Harman; Tugay Ayasan; Eyüp Başer; Yasin Altay; Kürşat Akbulut (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to determine effects of different dietary rosemary essential oil levels on growth performance, carcass traits and haematological values of breeder chukar partridge. Eighty (60 females and 20 males), 32-week-old breeder chukar partridge were randomly divided in five treatments, with four replicate pens with 4 birds each. Five experimental diets were formulated according to rosemary essential oil inclusion rates 0 mg/kg, 24 mg/kg, 48 mg/kg, 72 mg/kg and 96 mg/kg, respectively. The experiment lasted for 8 weeks. The chukar partridges had free access to ad libitum feed and water. At the end of the trial, 1 male and 1 female partridge were slaughtered for blood analysis. The obtained results showed that there was no significant difference in feed intake, body weight gain between the control and treatment groups. Dietary rosemary essential oil supplementation did not affect blood serum glucose, urea, triglyceride, total cholesterol, HDL-C and LDL-C levels in breeder Chukar partridges. It could be concluded that supplementing rosemary essential oil into Chukar partridges diet show no negative effect on growth performance.